OP0103 DOES GENDER, AGE OR SUBPOPULATION INFLUENCE THE MAINTENANCE OF CLINICAL REMISSION IN AXIAL SPONDYLOARTHRITIS FOLLOWING CERTOLIZUMAB PEGOL DOSE REDUCTION?. (2nd June 2020) - Landewé, R. B. M.; Van der Heijde, D.; Dougados, M.; Baraliakos, X.; Van den Bosch, F.; Gaffney, K.; Bauer, L.; Hoepken, B.; De Peyrecave, N.; Thomas, K.; Gensler, L. S.
Abstract : Background: Previous studies have shown that withdrawing tumour necrosis factor inhibitors (TNFi) in patients (pts) with axial spondyloarthritis (axSpA) who have achieved sustained remission often leads to relapse. 1 However, none have formally tested TNFi dose reduction strategies in a broad axSpA population or evaluated whether relapse following TNFi dose reduction and withdrawal is associated with a specific demographic subgroup. Objectives: C-OPTIMISE evaluated the percentage of pts without flare after TNFi dose continuation, reduction or withdrawal in adults with early axSpA treated with the Fc-free, PEGylated TNFi certolizumab pegol (CZP). Here, we analyse whether responses to reduced maintenance dose were comparable in pts stratified by axSpA subpopulation, gender and age. Methods: C-OPTIMISE (NCT02505542 ) was a multicentre, two-part phase 3b study in adults with early (<5 years' symptom duration) active axSpA (stratified for radiographic [r]- and non-radiographic [nr]- axSpA). Pts received CZP 200 mg every 2 weeks (wks) (Q2W; 400 mg loading dose at Wks 0, 2 and 4) during the open-label induction period. At Wk 48, pts in sustained remission (Ankylosing Spondylitis Disease Activity Score [ASDAS] <1.3 at Wk 32 or 36 [if ASDAS <1.3 at Wk 32, it must be <2.1 at Wk 36, or vice versa] and at Wk 48) were randomised to double-blind full maintenance dose (CZP 200 mg Q2W); reduced maintenance dose (CZP 200 mg every 4 wks [Q4W]) or placebo (PBO) for a further 48 wks (maintenance period). The primary endpoint was the percentage of pts not experiencing a flare (ASDAS ≥2.1 at two consecutive visits or ASDAS >3.5 at any timepoint) during Wks 48–96. Analyses were conducted on subgroups according to axSpA subpopulation, gender and age ≤/> the median age of the randomised set (32 years). Results: During the 48-wk induction period, 43.9% of patients (323/736) achieved sustained remission and 313 pts entered the 48-wk maintenance period (r/nr-axSpA: 168/145 pts; males/females: 247/66 pts; age ≤32/>32: 165/148 pts). During the maintenance period, responses in r- and nr-axSpA pts were comparable across all three randomised arms. 83.9% r-axSpA and 83.3% nr-axSpA pts receiving the full CZP maintenance dose did not experience a flare, and in the reduced maintenance dose arm 82.1% r-axSpA and 75.5% nr-axSpA pts did not experience a flare. In the PBO group this was reduced to 17.9% and 22.9%, respectively. Similar responses were seen in pts stratified by gender or age, with substantially higher percentages of pts randomised to CZP full or reduced maintenance dose remaining free of flares compared to PBO in all subgroups (Figure). Conclusion: The results of C-OPTIMISE indicate that a reduced maintenance dose is suitable for pts with axSpA who achieve sustained remission following 1 year of CZP treatment, regardless of axSpA subpopulation, gender or age. Complete treatment withdrawal is not recommended due to the high risk of flare. References: [1 ]Landewe R. Lancet 2018;392:134–44. Acknowledgments: This study was funded by UCB Pharma. Editorial services were provided by Costello Medical Disclosure of Interests: Robert B.M. Landewé Consultant of: AbbVie; AstraZeneca; Bristol-Myers Squibb; Eli Lilly & Co.; Galapagos NV; Novartis; Pfizer; UCB Pharma, Désirée van der Heijde Consultant of: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead Sciences, Inc., Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma; Director of Imaging Rheumatology BV, Maxime Dougados Grant/research support from: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Consultant of: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Speakers bureau: AbbVie, Eli Lilly, Merck, Novartis, Pfizer and UCB Pharma, Xenofon Baraliakos Grant/research support from: Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Consultant of: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB and Werfen, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Karl Gaffney Grant/research support from: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Consultant of: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Speakers bureau: AbbVie, Celgene, MSD, Novartis, Pfizer, and UCB Pharma, Lars Bauer Employee of: UCB Pharma, Bengt Hoepken Employee of: UCB Pharma, Natasha de Peyrecave Employee of: UCB Pharma, Karen Thomas Employee of: UCB Pharma, Lianne S. Gensler Grant/research support from: Pfizer, Novartis, UCB, Consultant of: AbbVie, Eli Lilly, GSK, Novartis, UCB